The Practice of Tabut in Bengkulu: A Shared Tradition of Sunni And Shia - Femalia Valentine; Idi Warsah; Ruly Morganna; Mirzon Daheri (Graduate Program of Pontianak Institute of Islamic Studies, 2021)
This study explains how the existence of Tabut is interpreted so that it becomes a tradition in the Sunni’s community. It is important to understand how this ritual is maintained in the midst of the Sunni-Shia’s conflicts which continue to occur. The present study was qualitatively conducted using a field research method. The members including the leaders of Keluarga Kerukunan Tabut (KKT) and those of Tabut Pembangunan as the community handled by the government were engaged as the participants of this study. The data collection techniques deployed interviews, observations, documentation, and literature reviews. The present study revealed that the existence of Tabut’s tradition which is claimed to be a tradition originated from Shia’s teachings is able to maintain its presence in Bengkulu. This existence survives in the middle of Bengkulu’s society that is predominantly Sunni. This tradition is capable of being a peaceful path between Sunni and Shia in Bengkulu because each of them succeeds in creating social interactions through the Tabut’s tradition as human relations and the symbol they interpret. As an implication, this study highlighted that a religious or cultural activity can be a medium of social bondage in the midst of cultural diversity. This study contributes to being a reference for those who have interests in anthropological, social, and religious fields.